2020
DOI: 10.21203/rs.3.rs-19224/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Correlation of Online Health Information Seeking Experience with the Health Related Quality of Life: A Cross-sectional Study among Iranian Female Students

Abstract: Background: Given the increasing availability of internet, it has become a common source of health information for all population including students. However, the actual effect of this increased access to information on the health status and its different aspects needs to be studied more. This study aimed to investigate the correlations between online health information seeking behavior and health related quality of life in a sample of high school students of Iran. Methods: A survey was conducted among seconda… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…This paper describes online health informationseeking skills (OHISS) and its related factors in middle-aged people. Our study revealed that participants had a level of average the online health information-seeking skills which is similar to the studies conducted in other countries such as China and the United States [22][23][24]. In the country of Ghana, few patients use online health information [25].…”
Section: Discussionsupporting
confidence: 83%
“…This paper describes online health informationseeking skills (OHISS) and its related factors in middle-aged people. Our study revealed that participants had a level of average the online health information-seeking skills which is similar to the studies conducted in other countries such as China and the United States [22][23][24]. In the country of Ghana, few patients use online health information [25].…”
Section: Discussionsupporting
confidence: 83%